Sometimes Always True : Undogmatic Pluralism in Politics, Metaphysics, and Epistemology - Barris, Jeremy (Book collections on Project MUSE., 2015)
This title aims to resolve three connected problems. First, we need an undogmatic pluralist standpoint in political theory, epistemology, and metaphysics. But genuine pluralism suffers from the contradiction that making room for fundamental differences in outlook means making room for outlooks that exclude pluralism. Second, philosophy involves reflecting on the world and meaning as a whole, yet this means adopting a vantage point in some way outside of meaning. Third, our lived experience of the sense of our lives similarly undermines its own sense, as it involves having a vantage point in some way wholly outside ourselves.